In silico mapping of the dynamic interactions and structure-activity relationship of flavonoid compounds against the immune checkpoint programmed-cell death 1 pathway - Sartori, Geraldo Rodrigues; Albuquerque, Aline de Oliveira; Santos-Costa, Andrielly Henriques; Andrade, Luca Milério; Almeida, Diego da Silva; Gaieta, Eduardo Menezes; Sampaio, Jean Vieira; Albuquerque, Vitória Taiana de Melo Lima; Martins Da Silva, João Hermínio (Frontiers in Drug Discovery, 2022)
Flavonoids are a class of natural products widely available in medicinal and dietary plants. Their pharmacological use has shown the potential to reduce the risk of different types of cancer, among other prevalent diseases. Their molecular scaffold inhibits the PD-1/PD-L1 axis, an important pathway related to the adaptive immune resistance of cancer cells already targeted for developing new cancer immunotherapy. However, despite the availability of kinetic and thermodynamic experimental data on the flavonoid–PD-1/PD-L1 interaction, there is still a lack of reliable information about their binding mode at the atomic level. Thus, we aimed to computationally predict the binding mode of flavonoid molecules with PD-1 and/or PD-L1 proteins using unbiased computational methodologies such as blind docking and supervised molecular dynamics simulation. The molecular interactions and dynamics of these predicted poses of protein-flavonoid complexes were further analyzed through multiple molecular dynamics simulations. This information, corroborated with the IC50 and KD values from available literature, was used to perform molecular matched-pair analysis to comprehensively describe the main interactions governing the inhibition of the complex PD-1/PD-L1 by the flavonoid scaffold. By analyzing the effect of substitutions in such a scaffold, we observed a clear correspondence with literature binding assays. Thus, we propose, for dimeric PD-L1, that the 7-O-glucoside forces the molecule displacement in the dimer interface. Furthermore, the 3-OH plays an essential role in stabilizing the buried binding mode by water-bridged hydrogen bonds with Asp122 and Gln66 in both extremities of the pocket. In PD-1, we suggest that flavonoids could bind through the BC loop by inducing a flip of Phe56 after a conformational change of the Asn58 glycosylation. Hence, our results introduced unprecedented information on flavonoid interaction and dynamics when complexed with PD-1 checkpoint pathway proteins and can pave the road for developing new flavonoid derivatives with selective anticancer activity.